Radial access mechanical thrombectomy: bail-out approach in patients with total abdominal aorta occlusion - a case report - Shamsuddin Perisamy, Rajeev; Muda, Ahmad Sobri; Kamis, Mohd Fandi Al-Khafiz; Tharek, Anas; Md Noh, Mohamad Syafeeq Faeez (Georg Thieme Verlag, 2025)
Radial artery access for mechanical thrombectomy is emerging as a viable alternative to femoral access, particularly in patients with challenging vascular anatomy. This case report describes a successful mechanical thrombectomy via the radial approach in a patient with an acute ischemic stroke. The technical feasibility, procedural outcomes, and potential advantages of this approach are discussed.